Pengaruh Motivasi, Lingkungan Kerja Fisik dan Kepemimpinan Terhadap Kepuasan Kerja Karyawan - Ratnasari, Ni Putu Intan; Kartika Dewi, Anak Agung Sagung (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
Job satisfaction is a condition when employees can feel a sense of happy and unhappy when doing their job. The aims of this study is to determine the effect of motivation, physical work environment and leadership on job satisfaction of employees at the Dinas Tenaga Kerja dan Transmigrasi Kabupaten Tabanan. The number of respondents as many as 46 people,this locations has been chosen because in this location have associated problems of motivation, leadership and working conditions that affected to employee satisfaction. The data collection was done by distributing questionnaires to 46 respondents and one of the respondents is the leaders, so that are not included in the data collection. Data were analyzed with multiple linear regression analysis techniques that previously have passed the test of classical assumptions. The results show that these variables have positive and significant affect, both simultaneously and partially on job satisfaction. Besides motivation is the dominant variable affecting job satisfaction of employees at the Dinas Tenaga Kerja dan Transmigrasi Kabupaten Tabanan. Judging from the analysis the results, then the company should pay more attention to employee comfort. Keywords: motivation , physical work environment, leadership, job satisfaction
Keywords: Keywords: motivation, physical work environment, leadership, job satisfaction